The Role of Tourism Development on CO2 Emission Reduction in an Extended Version of the Environmental Kuznets Curve: Evidence from Top Tourist Destination Countries - Senyücel, Elif (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The link among energy consumption, environmental pollution, and economic growth has been long investigated. Nevertheless, the trade off between energy consumption and environment quality needs more attention, especially tourism development based on the concept of International tourism. Tourism development is center of economic growth across the countries. This thesis empirically investigates the role of tourism development in an extended version of Environmental Kuznets Curve (EKC) for top 50 tourist destination countries. Panel data on annual basis that range from 1996 to 2016 have been used through employing CADF, CIPS and PANKPSS unit root tests, DSUR cointegrating test as well as DH panel dynamic causality test. The Results explain that tourism development exerts significant long-term effects on the extended version of EKC whereas carbon emissions level significantly move over years through tourism development. Energy is an important indicator of development in national economies. The fact that energy needs are consumed from fossil energy sources is an important factor that increases carbon dioxide (CO2) emissions, an indicator of environmental pollution. Especially in developed countries, with the widespread use of renewable energy sources, the damage caused by industrialization to the environment is minimized, but developing countries consume energy without considering the damage they cause to the environment. Our findings also indicate that tourism development has positive effects on the level of CO2 emissions in the case of Turkey, Thailand, Russia, Greece, Saudi Arabia, Macao, Indonesia, Brazil, Dominica, Philippines, Bulgaria, Tunisia, Egypt, Iran, Georgia, Hong Kong, India and Malaysia. Developing countries have higher carbon emissions than developed countries. This result suggests that these countries should not use traditional fuel oil consumption methods and such methods need to be abandoned for reduction of carbon dioxide in terms of environmental quality and sustainability. It is seen that technological progress increases CO2 emissions in China.

ÖZ: Enerji tüketimi, çevre kirliliği ve ekonomik büyüme arasındaki bağlantı uzun süredir araştırılmaktadır. Bununla birlikte, enerji tüketimi ve çevre kalitesi arasındaki dengeye, özellikle de Uluslararası turizm kavramına dayalı turizm gelişimine daha fazla dikkat edilmesi gerekmektedir. Turizm gelişimi, ülkeler arasında ekonomik büyümenin merkezidir. Bu tez, en iyi 50 turistik destinasyon ülkesi için Çevresel Kuznets Eğrisinin (EKC) genişletilmiş bir versiyonunda turizm gelişiminin rolünü ampirik olarak araştırmaktadır. CADF, CIPS ve PANKPSS birim kök testleri, DSUR eşbütünleşme testi ve DH panel dinamik nedensellik testi kullanılarak 1996 ile 2016 yılları arasında değişen yıllık bazda panel veriler kullanılmıştır. Sonuçlar, turizm gelişiminin EKC'nin genişletilmiş versiyonu üzerinde önemli uzun vadeli etkiler uyguladığını, ancak karbon emisyonlarının yıllar içinde turizm gelişimi yoluyla önemli ölçüde hareket ettiğini açıklamaktadır. Ülke ekonomilerinde kalkınmanın önemli bir göstergesi enerjidir. Enerji ihtiyaçlarının fosil enerji kaynaklarından tüketiliyor olması önemli bir çevre kirliliğinin göstergesi karbondioksit (CO2) emisyonunu artıran önemli bir unsurdur. Özellikle gelişmiş ülkelerde yenilenebilir enerji kaynaklarının kullanımının yaygınlaşması ile sanayileşmenin çevreye verdiği zarar minimize edilmektedir ancak gelişmekte olan ülkeler çevreye verdikleri zararı dikkate almadan enerji tüketimi yapmaktadırlar. Bulgularımız aynı zamanda turizm gelişiminin Türkiye, Tayland, Rusya, Yunanistan, Suudi Arabistan, Makao, Endonezya, Brezilya, Dominika, Filipinler, Bulgaristan, Tunus, Mısır, İran, Gürcistan, Hong Kong, Hindistan ve Malezya örneğinde CO2 emisyonları düzeyi üzerinde olumlu etkileri olduğunu göstermektedir. Gelişmekte olan ülkelerin karbon emisyon düzeyi gelişmiş ülkelere göre yüksek olmaktadır. Bu ülkelerin geleneksel akaryakıt tüketim yöntemlerini kullanmamaları gerektiğini ve çevresel kalite ve sürdürülebilirlik açısından karbondioksitin azaltılması için bu tür yöntemlerin terk edilmesi gerektiğini göstermektedir.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Supervisor: Prof. Dr. Sami Fethi
Keywords: Tourism--Tourism Development--CO2 Emission; Tourism development; Carbon emissions; EKC model; Panel data analysis; Top 50 Tourist Destinations